THE PLACE AND DEVELOPMENT TRENDS OF PHRASEOLOGY IN MODERN LINGUISTIC THEORIES - Zokirova Sevara, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
The thesis provides an in-depth review of the role and development trends of phraseology in modern linguistic theories. The evolution of phraseology is analyzed based on the theories of cognitive linguistics, anthropocentrism, and multimodality, and the cognitive and cultural layers of language are highlighted through the Sapir-Whorf hypothesis, Lakoff-Johnson metaphor theory, and Perlman multimodality models. Trends are discussed in detail under the influence of digital communication, globalization, corpus analysis, and machine learning. The results present phraseology as a central element in future models of language, emphasizing neurolinguistics and evolutionary linguistics, which offer new approaches for modern research.